Conceptual Understanding of Translanguaging: - Faisal Arafat (Crossings)
Following a qualitative approach and a ‘critical postpositivistic’ paradigm, this study attempted to explore the conceptual familiarity of translanguaging among five English teachers (female 2, male 3) of higher secondary level (grade 11 & 12) coming from five different demographic backgrounds in Bangladesh. Research data was collected through in-depth semi-structured interviews and was processed later by following the ‘general inductive approach’ to develop some themes. Narrative analysis of the themes was presented to show the insights or the findings, revealing that none of the teachers had any conceptual clarity on translanguaging - only one among the five participants had heard about the term ‘translanguaging’ before they had been contacted for the interviews. However, during the interviews - all the participants gradually opined that, though they had been unaware about the conceptual technicalities of translanguaging, they had always been practicing and using it in their classrooms considering it mostly beneficial for the students.